Glucocorticoid Sensitivity Is Highly Variable in Critically Ill Patients With Septic Shock and Is Associated With Disease Severity*. Issue 6 (June 2016) - Cohen, Jeremy; Pretorius, Carel J.; Ungerer, Jacobus P. J.; Cardinal, John; Blumenthal, Antje; Presneill, Jeff; Gatica-Andrades, Marcela; Jarrett, Paul; Lassig-Smith, Melissa; Stuart, Janine; Dunlop, Rachel; Starr, Therese; et al.
Abstract : Objectives: To measure tissue glucocorticoid sensitivity in patients with septic shock and determine its relationship to standard measurements of adrenal function and of outcome. Design: Prospective observational trial. Setting: Teaching hospital ICU. Subjects: Forty-one patients and 20 controls were studied. Interventions: Glucocorticoid sensitivity was measured by in vitro suppression of cytokine production from lipopolysaccharide-stimulated leukocytes. Measurements and Main Results: There was no significant difference between the groups in the relative suppression of cytokine production, although there was a greater range and variance in the patient data. Patients in the lowest quartile of glucocorticoid sensitivity had higher Acute Physiology and Chronic Health Evaluation II scores (25 [24–28] vs 20 [14–23]; p = 0.02) and a trend toward higher mortality (30% vs 0%; p = 0.2) compared to those in the highest. The mRNA expression of the β variant of the glucocorticoid receptor and the 11-β hydroxysteroid dehydrogenase 2 isozyme were significantly higher in patients compared to controls (8.6-fold, p = 0.002 and 10.1-fold, p = 0.0002, respectively). Changes in mRNA expression of these genes did not correlate with measurements of glucocorticoid sensitivity. Conclusions: Patients with septic shock and controls do not differ in their median glucocorticoid sensitivity. However, patients exhibited a greater variability in glucocorticoid responsiveness and had evidence of association between increased sickness sensitivity and reduced glucocorticoid sensitivity. Sensitivity to glucocorticoids did not appear to be mediated by changes in the expression of the β variant of the glucocorticoid receptor or the 11-β hydroxysteroid dehydrogenase 2 isozyme.